THE FORMATION OF READING LITERACY OF STUDENTS IN ENGLISH LANGUAGE TEACHING (International Conference on Economics, Finance, Banking and Management, 2025)
Today, teaching foreign languages from an early age is considered one of the important issues in education systems around the world. The process of learning a language in primary school should not be limited to studying grammar alone, but should also be carried out through developing students’ communication skills and teaching them to speak freely and confidently. During foreign language learning, it is essential to use game technologies, interactive methods, as well as visual and audio materials in order to make lessons engaging and lively. This article highlights the issues of developing students’ logical thinking abilities, improving fluency, and forming skills of giving quick and accurate answers through modern approaches and innovative methods in teaching English in primary school. In addition, it analyzes methods that serve to increase students’ interest in knowledge, develop independent thinking, and foster a creative approach. Recommendations are also provided on how to enhance teaching effectiveness through interactive and game-based methods.